Effect of 3 Preservation Methods (Freezing, Cryopreservation, and Freezing + Irradiation) on Human Menisci Ultrastructure: An Ex Vivo Comparative Study With Fresh Tissue as a Gold Standard. Issue 12 (October 2018) - Jacquet, Christophe; Erivan, Roger; Argenson, Jean-Noël; Parratte, Sebastien; Ollivier, Matthieu
Background: Three main meniscus preservation methods have been advocated: freezing (–80°C), freezing with gamma irradiation (–80°C + 25 kGy), and cryopreservation (–140°C). Hypothesis: All preservation methods will result in structural and architectural properties similar to those of fresh meniscus, defined as the gold standard. Study Design: Controlled laboratory study. Methods: Five human intact menisci were collected from 5 patients undergoing total knee arthroplasty. The inclusion criteria were patients <70 years old with primary unilateral (medial) femorotibial knee osteoarthritis and without surgical or traumatic history on the operated knee. Four cubes (9 mm 3 ) were cut inside of the white, or avascular, area of each specimen's middle horn and divided into 4 groups: "fresh" control, frozen (–80°C), cryopreserved (–140°C), and frozen + irradiated (–80°C + 25 kGy). Specimens of the control group were evaluated at day 1, and specimens from the frozen, cryopreserved, and frozen + irradiated groups were evaluated after 1 month of storage. Evaluation was performed with electron microscopy according a validated protocol to analyze (1) mean diameters of the collagen fibers in longitudinal and transverse sections in 5 points per section and (2) validated architectural scores. Results: No significant difference was found between the control and cryopreserved groups regarding mean transverse and longitudinal diameters (transverse: 95.39 ± 15.87 nm vs 99.62 ± 19.23 nm, P = .1; longitudinal: 96.31 ± 13.96 nm vs 94.57 ± 16.42 nm, P = .1). Significant differences were found between the control and frozen groups (transverse: 95.39 ± 15.87 nm vs 70.20 ± 13.94 nm, P < .001; longitudinal: 96.31 ± 13.96 nm vs 71.28 ± 10.64 nm, P < .001) and the control and frozen + irradiated groups (transverse: 95.39 ± 15.87 nm vs 63.1 ± 15.57 nm, P < .001; longitudinal: 96.31 ± 13.96 nm vs 60.9 ± 14.8 nm, P < .001). Regarding architectural score calculation, there were significant differences between the control and frozen groups (4.5 ± 1.3 vs 2.3 ± 1.4, P = .02) and the control and frozen + irradiated groups (4.5 ± 1.3 vs 1.4 ± 0.9, P = .02). Conclusion: Cryopreservation is the only method that preserves fresh meniscus architectural specificities. Freezing and freezing + irradiation methods modify histologic properties of meniscal allograft. Irradiation deeply alters diameters and the organization of collagen fibers, and this method should be used with caution to preserve and sterilize meniscus tissue. Clinical Relevance: The results of our study exhibited detrimental effects of simple freezing and freezing + irradiation on the collagen network of sample meniscus. If those effects occur in menisci prepared for allograft procedures, important differences could appear on the basis of the preservation procedure in terms of the graft's mechanical properties and, thus, the patient's outcomes.